2011
DOI: 10.1016/j.ejcts.2010.10.003
|View full text |Cite
|
Sign up to set email alerts
|

The Papworth Bleeding Risk Score: a stratification scheme for identifying cardiac surgery patients at risk of excessive early postoperative bleeding

Abstract: We have developed a simple risk stratification score that can separate, preoperatively, patients into risk groups with markedly different rates of severe postoperative bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
86
1
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(91 citation statements)
references
References 23 publications
0
86
1
4
Order By: Relevance
“…However, before the risk stratification model can be used clinically, it needs to be prospectively validated. Specifically, additional confirmatory studies are required to ensure that the prevalence reported by our model is accurate ("calibration") and that our stratification schema can reliably discern css at low and high risk of cvd ("discrimination") 23 . Similar attempts to design a prediction algorithm akin to our simple risk stratification schema have been made in the past.…”
Section: Discussionmentioning
confidence: 99%
“…However, before the risk stratification model can be used clinically, it needs to be prospectively validated. Specifically, additional confirmatory studies are required to ensure that the prevalence reported by our model is accurate ("calibration") and that our stratification schema can reliably discern css at low and high risk of cvd ("discrimination") 23 . Similar attempts to design a prediction algorithm akin to our simple risk stratification schema have been made in the past.…”
Section: Discussionmentioning
confidence: 99%
“…These identify age, female sex, low body mass index (BMI), preoperative anaemia, chronic kidney disease, poor left ventricular function and recent myocardial ischaemia as predictive of excessive bleeding or MBT. 63,64 The mechanism by which these factors contribute to bleeding is poorly understood. Existing scores are not widely used because of the limited generalisability of risk models developed in single centres or subpopulations of patients.…”
Section: Preoperative Morbiditymentioning
confidence: 99%
“…In addition to standard care, current blood management guidelines recommend (class 1, level of evidence C 24 ) that patients undergo a formal assessment and documentation of bleeding risk. Risk scores that may accurately predict the risk of bleeding and red cell transfusion exist; 63,64,88,89 however, these are not widely used. The predictive accuracy of any new diagnostic test should therefore complement appropriate clinical assessment and the benefits of additional testing should be assessed beyond those attributable to clinical assessment combined with standard testing.…”
Section: Point-of-care Coagulation and Platelet Testing In Cardiac Sumentioning
confidence: 99%
See 1 more Smart Citation
“…Recurrent factors associated with increased bleeding risk are underweight patients, re-do and complex procedures (e.g. multiple valve replacements or operations involving the aortic arch), as well as emergency operations [1,15,16].…”
Section: Causes Of Excessive Bleedingmentioning
confidence: 99%